Aminothiazoles inhibit RANKL‐ and LPS‐mediated osteoclastogenesis and PGE2 production in RAW 264.7 cells. Issue 6 (14th March 2016) - Kats, Anna; Norgård, Maria; Wondimu, Zenebech; Koro, Catalin; Concha Quezada, Hernán; Andersson, Göran; Yucel‐Lindberg, Tülay
Abstract: Periodontitis is characterized by chronic inflammation and osteoclast‐mediated bone loss regulated by the receptor activator of nuclear factor‐κB (RANK), RANK ligand (RANKL) and osteoprotegerin (OPG). The aim of this study was to investigate the effect of aminothiazoles targeting prostaglandin E synthase‐1 (mPGES‐1) on RANKL‐ and lipopolysaccharide (LPS)‐mediated osteoclastogenesis and prostaglandin E2 (PGE2 ) production in vitro using the osteoclast precursor RAW 264.7 cells. RAW 264.7 cells were treated with RANKL or LPS alone or in combination with the aminothiazoles 4‐([4‐(2‐naphthyl)‐1, 3‐thiazol‐2‐yl]amino)phenol (TH‐848) or 4‐(3‐fluoro‐4‐methoxyphenyl)‐ N ‐(4‐phenoxyphenyl)‐1, 3‐thiazol‐2‐amine (TH‐644). Aminothiazoles significantly decreased the number of multinucleated tartrate‐resistant acid phosphatase (TRAP)‐positive osteoclast‐like cells in cultures of RANKL‐ and LPS‐stimulated RAW 264.7 cells, as well as reduced the production of PGE2 in culture supernatants. LPS‐treatment induced mPGES‐1 mRNA expression at 16 hrs and the subsequent PGE2 production at 72 hrs. Conversely, RANKL did not affect PGE2 secretion but markedly reduced mPGES‐1 at mRNA level. Furthermore, mRNA expression of TRAP and cathepsin K (CTSK) was reduced by aminothiazoles in RAW 264.7 cells activated by LPS, whereas RANK, OPG or tumour necrosis factor α mRNA expression was not significantly affected. In RANKL‐activated RAW 264.7 cells, TH‐848 and TH‐644 down‐regulated CTSK but not TRAP mRNA expression. Moreover, the inhibitory effect of aminothiazoles on PGE2 production was also confirmed in LPS‐stimulated human peripheral blood mononuclear cell cultures. In conclusion, the aminothiazoles reduced both LPS‐ and RANKL‐mediated osteoclastogenesis and PGE2 production in RAW 264.7 cells, suggesting these compounds as potential inhibitors for treatment of chronic inflammatory bone resorption, such as periodontitis.